MPP8 and SIRT1 crosstalk in E‐cadherin gene silencing and epithelial–mesenchymal transition. (13th April 2015) - Sun, Lidong; Kokura, Kenji; Izumi, Victoria; Koomen, John M; Seto, Edward; Chen, Jiandong; Fang, Jia
Abstract As a critical developmental process, epithelial–mesenchymal transition (EMT) involves complex transcriptional reprogramming and has been closely linked to malignant progression. Although various epigenetic modifications, such as histone deacetylation and H3K9 methylation, have been implicated in this process, how they are coordinated remains elusive. We recently revealed that MPP8 couples H3K9 methylation and DNA methylation for E‐cadherin gene silencing and promotes tumor cell migration, invasion, and EMT. Here, we show that MPP8 cooperates with the class III HDAC SIRT1 in this process through their physical interaction. SIRT1 antagonizes PCAF‐catalyzed MPP8‐K439 acetylation to protect MPP8 from ubiquitin‐proteasome‐mediated proteolysis. Conversely, MPP8 recruits SIRT1 for H4K16 deacetylation after binding to methyl‐H3K9 on target promoters. Consequently, disabling either MPP8 methyl‐H3K9 binding or SIRT1 interaction de‐represses E‐cadherin and reduces EMT phenotypes, as does knockdown of MPP8 or SIRT1 in prostate cancer cells. These results illustrate how SIRT1 and MPP8 reciprocally promote each other's function and coordinate epithelial gene silencing and EMT.